Polyoxometallate catalyst, preparation method and application of polyoxometallate catalyst in electrocatalytic synthesis of ammonia

A polyoxometalate catalyst with a cage-like structure addresses the limitations of noble and transition metal catalysts, achieving high ammonia yield and efficiency in nitrate reduction to ammonia synthesis.

CN119243215APending Publication Date: 2025-01-03LIAONING NORMAL UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411322519.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing noble metal-based electrocatalysts for nitrate reduction to ammonia are costly, have poor chemical stability, and weak adsorption capacity for nitrogen fixation intermediates, while transition metal electrocatalysts face challenges in electrocatalytic ammonia synthesis due to low electroactivity.

Method used

A polyoxometalate catalyst is developed, composed of metal organic ligands and POMs, forming a cage-like zero-dimensional structure with POMs wrapped by metal organic ligands, using transition metal elements combined with carboxylated imidazole ligands, and prepared via a one-step hydrothermal method.

Benefits of technology

The catalyst achieves high ammonia production yield and Faraday efficiency, with yields up to 1.49 mmol/h/mg and Faraday efficiency up to 99.37%, addressing the limitations of existing catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243215A_ABST
    Figure CN119243215A_ABST
Patent Text Reader

Abstract

The invention discloses a polyoxometallate catalyst, a preparation method and an application of the polyoxometallate catalyst in electrocatalytic synthesis of ammonia, a metal organic ligand is mainly formed by complexing carboxylated imidazole ligands and metal ions, and the catalyst with a cage-shaped zero-dimensional structure of polyoxometallate wrapped by the metal organic ligand is prepared by a one-step hydrothermal method. The preparation method is simple and easy to implement, and has excellent ammonia production Faraday efficiency and stable ammonia yield in the process of promoting the electrocatalytic reduction of nitrate to synthesize ammonia, the maximum ammonia yield can reach 1.49 mmol / h / mgcat, and the maximum Faraday efficiency can reach 99.37%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation and electrocatalytic nitrate reduction to ammonia production, and in particular to a polyoxometalate catalyst, a preparation method and application in electrocatalytic ammonia synthesis. Background Art

[0002] Ammonia (NH3) plays a vital role in modern industry and agriculture and has been widely used in the production of important chemicals such as fertilizers, fuels and medicines. In the past, the synthesis of ammonia mainly relied on the Haber-Bosch process with N2 and H2 as raw materials. However, breaking the N≡N triple bond requires a high energy (941 kJ / mol). The reaction process needs to be operated at high temperature (about 500℃) and high pressure (about 200atm), resulting in a large energy consumption, accounting for about 2% of the global annual energy supply. Nitrate is widely present in wastewater, especially one of the main nitrogen pollutants in groundwater. The accumulation of nitrate in the environment leads to an increase in the concentration of toxic nitrite converted from nitrate, which poses a serious threat to the safety of soil and groundwater. Therefore, removing nitrate from wastewater has become a top priority. The electrocatalytic technology is used to reduce nitrate to synthesize ammonia (NO3RR). Because breaking the weak N═O bond only requires 204 kJ / mol, it has the advantages of reducing energy consumption and reducing the cost of synthetic ammonia compared with the traditional Haber-Bosch ammonia synthesis process. The electrocatalytic nitrate reduction reaction is carried out in an H-type double-chamber reaction cell, wherein the cathode chamber and the anode chamber are separated by a proton exchange membrane, wherein the cathode chamber uses a hydrophobic carbon cloth loaded with a catalyst as a working electrode, an Ag / AgCl electrode as a reference electrode, and the anode chamber uses a carbon rod as a counter electrode; the anode electrolyte is a 0.1-2 mol / L H2SO4 solution, and the cathode electrolyte is a mixed solution including 0.01-2 mol / L KNO3 and 0.1-2 mol / L H2SO4. The nitrate in the cathode solution is subjected to an electrochemical reduction reaction to synthesize ammonia through constant potential polarization.

[0003] At present, various noble metal-based electrocatalysts, such as Rh, Ir, Pd, Ru and Pt, have been developed for different related reactions. However, they are difficult to use on a large scale due to their cost, raw material imports and poor chemical stability. Recently, transition metal-based catalysts have become potential candidates for NO3RR due to their good chemical stability, unique electronic structure and relatively low price. However, transition metal electrocatalysts have weak adsorption capacity for nitrogen fixation intermediates and poor electroactivity, making them difficult to be used in electrocatalytic synthesis of ammonia. Polyoxometalates (POMs) are a class of polymetallic oxygen cluster compounds formed by pre-transition metal ions connected by oxygen, which can be used as "electron sponges" with multi-electron redox properties. POMs have great potential in the field of catalysts due to their rich transition metal active sites and excellent redox ability. However, to date, there have been no reports on their application in electrocatalytic synthesis of ammonia by encapsulating them with metal organic ligands. Summary of the invention

[0004] The present invention aims to solve the above technical problems existing in the prior art and provides a polyoxometalate catalyst, a preparation method and an application in electrocatalytic synthesis of ammonia.

[0005] The technical solution of the present invention is: a polyoxometalate catalyst is a crystal composed of metal organic ligands and POMs, the crystal is a cage-like zero-dimensional structure in which POMs are wrapped by metal organic ligands, the metal organic ligands are transition metal elements combined with carboxylated imidazole ligands through coordination bonds, and the POMs are saturated, substituted and vacant Keggin-type tungsten or molybdenum polyacids.

[0006] The preferred technical solution is that the loading amount of the coordinated metal element in the crystal is 5-30% of the total mass of the catalyst.

[0007] A method for preparing the polyoxometalate catalyst as described above is carried out in the following steps:

[0008] Step 1. Dissolve a soluble inorganic metal salt and an imidazole ligand in an aqueous solution, react at 24-100° C. for 0.5-3 h to obtain a mixed solution A; the amount ratio of the soluble inorganic metal salt, the imidazole ligand and the aqueous solution is 0.1-1 mmol: 0.1-1 mmol: 6-8 mL;

[0009] Step 2. POMs is dissolved in water to obtain a POMs aqueous solution, and then the POMs aqueous solution is added dropwise to solution A, and reacted at 24-100° C. for 0.5-4 h to obtain a mixed solution B, wherein the dosage ratio of POMs to water is 0.02-2 mmol:6-8 mL, and the volume ratio of the POMs aqueous solution to the mixed solution A is 1:1;

[0010] Step 3. Add 0.1-2 mol / L nitric acid solution to the mixed solution B to adjust the pH value to 0-2, stir for 0.5-2h, transfer to a polytetrafluoroethylene-lined autoclave, place in an oven and heat at 60-180°C for 24-120h, take out, wash and dry to obtain the target catalyst.

[0011] A preferred technical solution is that the soluble inorganic metal salt is one or two of nitrate, chlorate, sulfate and acetate.

[0012] The preferred technical solution is to follow the following steps in sequence:

[0013] Step 1. Dissolve 0.2 mmol of AgNO3 and 0.1 mmol of 2,2'-biimidazole in 7 mL of aqueous solution and react at 80°C for 1 h to obtain a mixed solution A;

[0014] Step 2. 0.05 mmol PMo 10 V2 was dissolved in 7 mL of water to obtain a POMs aqueous solution, which was then added dropwise to solution A and reacted at 80 °C for 2 h to obtain a mixed solution B;

[0015] Step 3. Add 3 mL of 1.5 mol / L nitric acid solution to the mixed solution B to adjust the pH value to 0-2, stir for 0.5 h, transfer to a polytetrafluoroethylene-lined autoclave, and then place in an oven and heat at 120°C for 72 h. Take out, wash with deionized water 3-5 times in sequence, and dry in a vacuum oven at 60-80°C for 12-24 h to obtain the target catalyst.

[0016] An application of the above-mentioned polyoxometalate catalyst in electrocatalytic nitrate reduction to synthesize ammonia.

[0017] The present invention mainly forms a metal organic ligand by complexing a carboxylated imidazole ligand with a metal ion, and prepares a catalyst of a polyoxometalate coated with a metal organic ligand by a one-step hydrothermal method. The preparation method is simple and easy to implement, and has excellent ammonia production Faraday efficiency and stable ammonia yield in promoting the electrocatalytic reduction of nitrate to synthesize ammonia. The ammonia yield can reach up to 1.49mmol / h / mg. cat , the Faraday efficiency can reach up to 99.37%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a structural model diagram of the catalyst monomer prepared in Example 1 of the present invention.

[0019] Figure 2 This is a structural model diagram of the catalyst Ag3O2 cluster prepared in Example 1 of the present invention.

[0020] Figure 3It is a hydrogen bonding diagram of the catalyst prepared in Example 1 of the present invention.

[0021] Figure 4 This is a diagram of the number of polyacids around the Ag3O2 cluster of the catalyst prepared in Example 1 of the present invention.

[0022] Figure 5 It is a diagram showing the number of Ag3O2 clusters around the catalyst polyacid prepared in the embodiment of the present invention.

[0023] Figure 6 is a scanning electron microscope image of the catalyst prepared in Example 1 of the present invention.

[0024] Figure 7 It is the XRD diagram of the catalyst prepared in Examples 1-6 of the present invention.

[0025] Figure 8 The test graphs are cyclic voltammetry curves, linear sweep voltammetry curves and constant potential polarization curves of electrocatalytic nitrate reduction to synthesize ammonia using the catalyst prepared in Examples 1-6 of the present invention as the working electrode.

[0026] Fig. 9 Schematic diagram of the yield and Faraday efficiency of electrocatalytic nitrate reduction to synthesize ammonia using the catalyst prepared in Examples 1-6 of the present invention as the working electrode. DETAILED DESCRIPTION

[0027] The present invention is described in detail below by specific examples. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial sources.

[0028] There is no particular limitation on the purity of all raw materials in the present invention, but analytically pure materials are preferably used in the present invention.

[0029] Embodiment 1:

[0030] The preparation method of the polyoxometalate catalyst of the present invention is carried out in the following steps:

[0031] Step 1. Dissolve 0.2 mmol of AgNO3 and 0.1 mmol of 2,2'-biimidazole (H2biim) in 7 mL of aqueous solution and react at 80°C for 1 h to obtain a mixed solution A;

[0032] Step 2. 0.05 mmol PMo 10 V2 was dissolved in 7 mL of water to obtain a POMs aqueous solution, which was then added dropwise to solution A and reacted at 80 °C for 2 h to obtain a mixed solution B;

[0033] Step 3. Add 3 mL of 1.5 mol / L nitric acid solution to the mixed solution B to adjust the pH value to 0-2, stir for 0.5 h, transfer to a polytetrafluoroethylene-lined autoclave, place in an oven and heat at 120°C for 72 h, take out, wash with deionized water 3-5 times, and dry in a vacuum oven at 60-80°C for 12-24 h to obtain the target catalyst, named L-PMo 10 V2.

[0034] L-PMo 10 The V2 monomer structure model is shown in the figure Figure 1 As shown. Figure 1 It can be seen that: the metal organic ligand and PMo 10 V2 crystal, the crystal is PMo 10 V2 is a cage-like zero-dimensional structure wrapped by metal-organic ligands, which are transition metal elements Ag combined with H2biim through coordination bonds.

[0035] The structural model diagram of the catalyst Ag3O2 cluster prepared in Example 1 of the present invention is as follows Figure 2 As shown in the figure, it can be seen that a unique Ag3O2 cluster is formed in the compound structure, in which three metal Ag + It exists in a triangular geometric configuration and is coordinated with one oxygen atom above and below the plane to form a trigonal bipyramidal geometric configuration.

[0036] The hydrogen bond representation diagram of the catalyst prepared in Example 1 of the present invention is as follows Figure 3 As shown, it can be seen that the organic ligand H2biim is carboxylated during the reaction. C3 and C5 in the H2biim structure are each connected to a carboxyl group, N1 and N3 are connected to two different silver ions in the form of coordination bonds, and the three carboxyl biimidazoles hold the Ag3O2 cluster in the center. The H on the N4 of the carboxyl biimidazole forms a hydrogen bond with the O on the nitrate.

[0037]

[0038] The number of polyacids around the Ag3O2 clusters of the catalyst prepared in Example 1 of the present invention is shown in FIG. Figure 4 As shown in the figure, it can be seen that three metal organic complexes hold one nitrate in the center and one metal organic complex is surrounded by three PMo 10 V2 group.

[0039] The number of Ag3O2 clusters around the catalyst polyacid prepared in Example 1 of the present invention is shown in FIG. Figure 5 As shown, it can be seen that 1 PMo 10 There are 6 metal organic complexes around the V2 group, and the 6 complexes form a spherical cavity to hold the PMo 10V2 is wrapped, that is, the compound is a zero-dimensional structure, and the polyacid groups are embedded in the central hole.

[0040] The SEM test image of the catalyst prepared in Example 1 of the present invention is as follows: Figure 6 As shown: The test results show that the catalyst prepared in Example 1 is a prismatic crystal.

[0041] Embodiment 2:

[0042] Steps 1 and 3 are the same as in Example 1;

[0043] The difference from Example 1 is step 2, specifically, 0.05 mmol SiW9 is dissolved in 7 mL water to obtain a POMs aqueous solution, and then the POMs aqueous solution is added dropwise to solution A, and reacted at 80°C for 2 h to obtain a mixed solution B. The obtained catalyst is named L-SiW 12 .

[0044] Embodiment 3:

[0045] Steps 1 and 3 are the same as in Example 1;

[0046] The difference from Example 1 is that step 2 is to add 0.05 mmol PW 11 Ag was dissolved in 7 mL of water to obtain a POMs aqueous solution, which was then added dropwise to solution A and reacted at 80 °C for 2 h to obtain a mixed solution B. The obtained catalyst was named L-PW 11 Ag.

[0047] Embodiment 4:

[0048] Steps 1 and 3 are the same as in Example 1;

[0049] The difference from Example 1 is that step 2 is to add 0.05 mmol PMo 12 Dissolve in 7 mL of water to obtain a POMs aqueous solution, then add the POMs aqueous solution dropwise to solution A and react at 80 °C for 2 h to obtain a mixed solution B. The obtained catalyst is named L-PMo 12 .

[0050] Embodiment 5:

[0051] Steps 1 and 3 are the same as in Example 1;

[0052] The difference from Example 1 is that step 2 is to add 0.05 mmol PMo 11 V was dissolved in 7 mL of water to obtain a POMs aqueous solution, which was then added dropwise to solution A and reacted at 80 °C for 2 h to obtain a mixed solution B. The obtained catalyst was named L-PMo 11 V.

[0053] Embodiment 6:

[0054] Steps 1 and 3 are the same as in Example 1;

[0055] The difference from Example 1 is that step 2 is to add 0.05 mmol PW 12 Dissolve in 7 mL of water to obtain a POMs aqueous solution, then add the POMs aqueous solution dropwise to solution A and react at 80 °C for 2 h to obtain a mixed solution B. The obtained catalyst is named L-PW 12 .

[0056] The X-ray powder diffraction patterns of Examples 1-6 of the present invention are as follows: Figure 7 Table 1 and Table 3 are crystallographic data tables of the above-mentioned Examples 1-3 and Examples 4-6.

[0057] Table 1

[0058]

[0059]

[0060] a R1=∑||F o |-|F c || / ∑|F o |, b wxya 2 =∑[w(F o 2 -F c 2 ) 2 ] / ∑[w(F o 2 ) 2 ] 1 / 2

[0061] Table 2

[0062]

[0063] a R1=∑||F o |-|F c || / ∑|F o |, b wxya 2 =∑[w(F o 2 -F c 2 ) 2 ] / ∑[w(F o 2 ) 2 ] 1 / 2

[0064] By performing X-ray diffraction analysis on the crystalline powder and processing the experimental data with the single crystal simulation data, it can be clearly seen from the comparison of the peak types of the two diffraction patterns that the two patterns are in good agreement, indicating that the catalyst prepared by the present invention has a high phase purity.

[0065] Experiment: Test of the electrocatalytic nitrate reduction performance of the catalyst of the present invention

[0066] Comparative Example 1:

[0067] 0.25 mg of silver powder and an equal amount of acetylene black were made into a slurry and sprayed onto the carbon cloth as a working electrode.

[0068] The experimental method is to use the catalysts prepared in Examples 1-6 and Comparative Example 1 for electrochemical testing. The specific operation method is as follows: a three-electrode system is used for testing, Ag / AgCl is used as a reference electrode, a carbon rod is used as a counter electrode, and a carbon cloth loaded with L-POMs is used as a working electrode. Cyclic voltammetry curves, linear scanning voltammetry curves and constant potential polarization curves are tested in 0.5 mol / L H2SO4 and 0.5 mol / L H2SO4+0.1 mol / L KNO3 systems, respectively. The results are shown in FIG. Figure 8 shown.

[0069] The ammonia yield and Faraday efficiency of each embodiment are as follows Fig. 9 As shown in Table 3.

[0070] Table 3

[0071]

[0072] pass Fig. 9 As can be seen from Table 3, compared with Comparative Example 1, the yields (Yield) and Faraday efficiencies (FE) of Examples 1-6 of the present invention are improved, especially Example 1 has the best effect, and the ammonia yield can reach 1.49 mmol / h / mg cat , the Faraday efficiency can reach 99.37%.

Claims

1. A polyoxometalate catalyst, characterized in that: The crystal is composed of metal organic ligands and POMs. The crystal is a cage-like zero-dimensional structure in which POMs are wrapped by metal organic ligands. The metal organic ligands are transition metal elements combined with carboxylated imidazole ligands through coordination bonds. The POMs are saturated, substituted and vacant Keggin-type tungsten or molybdenum polyacids.

2. The polyoxometalate catalyst according to claim 1, characterized in that: The loading amount of the coordinated metal element in the crystal is 5-30% of the total mass of the catalyst.

3. A method for preparing the polyoxometalate catalyst as claimed in claim 1 or 2, characterized in that Follow the steps below: Step 1. Dissolve a soluble inorganic metal salt and an imidazole ligand in an aqueous solution, react at 24-100° C. for 0.5-3 h to obtain a mixed solution A; the amount ratio of the soluble inorganic metal salt, the imidazole ligand and the aqueous solution is 0.1-1 mmol: 0.1-1 mmol: 6-8 ml; Step 2. POMs is dissolved in water to obtain a POMs aqueous solution, and then the POMs aqueous solution is added dropwise to solution A, and reacted at 24-100° C. for 0.5-4 h to obtain a mixed solution B, wherein the dosage ratio of POMs to water is 0.02-2 mmol:6-8 ml, and the volume ratio of the POMs aqueous solution to the mixed solution A is 1:1; Step 3. Add 0.1-2 mol / L nitric acid solution to the mixed solution B to adjust the pH value to 0-2, stir for 0.5-2h, transfer to a polytetrafluoroethylene-lined autoclave, place in an oven and heat at 60-180°C for 24-120h, take out, wash and dry to obtain the target catalyst.

4. The method for preparing a polyoxometalate catalyst according to claim 3, characterized in that: The soluble inorganic metal salt is one or two of nitrate, chlorate, sulfate and acetate.

5. The method for preparing a polyoxometalate catalyst according to claim 4, characterized in that: Follow the steps below: Step 1. Dissolve 0.2 mmol of AgNO3 and 0.1 mmol of 2,2'-biimidazole in 7 mL of aqueous solution and react at 80°C for 1 h to obtain a mixed solution A; Step 2. 0.05 mmol PMo 10 V2 was dissolved in 7 mL of water to obtain a POMs aqueous solution, which was then added dropwise to solution A and reacted at 80 °C for 2 h to obtain a mixed solution B; Step 3. Add 3 mL of 1.5 mol / L nitric acid solution to the mixed solution B to adjust the pH value to 0-2, stir for 0.5 h, transfer to a polytetrafluoroethylene-lined autoclave, and then place in an oven and heat at 120°C for 72 h. Take out, wash with deionized water 3-5 times in sequence, and dry in a vacuum oven at 60-80°C for 12-24 h to obtain the target catalyst.

6. Use of the polyoxometalate catalyst as claimed in claim 1 or 2 in electrocatalytic nitrate reduction to synthesize ammonia.

Citation Information

Cited By

  • Polyoxometallate nano-catalyst constructed by trinuclear ruthenium clusters and application of polyoxometallate nano-catalyst

    CN120967398A

  • Trinuclear ruthenium cluster constructed polyoxometalate nanocatalyst and application thereof

    CN120967398B